Firms' incentives to provide apprenticeships : studies on expected short- and longterm benefits - Jansen, Anika [Verfasser] (Research Centre for Education and the Labour Market, 2016)
"The contribution of firms is pivotal for the functioning of the dual system of apprenticeship training. Therefore, firm's incentive to train apprentices is an important field of research. Various studies have shown that the decision to train depends on the expected costs and benefits. Two major training benefits are short-term benefits in the form of productive contributions of apprentices and the long-term benefits in the form of a wedge between productivity and wages. It remained to be analyzed what in turn determines these benefits. This thesis analyzes a variety of framework conditions that act as such determinants." The main part comprises four empirical studies that deal with the following related research questions: (1) How are pre-training competencies that apprentices have obtained during their prior schooling related to apprentices' productivity at the workplace? (2) Do labor market regulations influence the expected post-training benefits and the organization of apprenticeship training? (3) Does the number of choice options in training curricula affect the supply of and demand for apprenticeships? (4) Are altruism and time preferences of decision-makers related to investments in apprenticeship training? (Excerpt, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 4.3.6 Human Capital; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 3.2 Unternehmen und Behörden; Betrieb; Ausbildungsbereitschaft; Anreizsystem; Bildungsertrag; Humankapital; Kosten-Nutzen-Analyse